Urgensi Penerapan Tes Insolvensi Atas Perusahaan Yang Akan Diputus Pailit (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
In the law embodied in Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, there isn't a requirement stipulating that a debtor must be declared unable (insolvent) to pay their debts through an insolvency test as a condition to determine their bankruptcy status or not. Instead, the debtor's bankruptcy status is established by proving that the debtor has a minimum of 2 (two) creditors, has failed to pay at least 1 (one) due and collectible debt. The absence of insolvency testing as a bankruptcy criterion in Indonesia could lead to companies that are actually capable of fulfilling their obligations being considered bankrupt because they meet the bankruptcy requirements in Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations regulates the requirements for bankruptcy. This has the potential for significant impact, even reducing the confidence of foreign investors to invest in Indonesia. This research employs a normative legal approach. The data source utilized in this study comprises secondary data obtained through the analysis of existing literature or documents. The results of insolvency testing, determining whether a company is categorized as insolvent or not, provide an opportunity for solvent debtors to prove that they have sufficient assets to settle debts to multiple creditors. This gives debtors the chance to rebuild their businesses. Therefore, the implementation of insolvency test in a company plays a role in saving solvent debtors from bankruptcy petitions filed by creditors.